2007
DOI: 10.1080/14631370701503174
|View full text |Cite
|
Sign up to set email alerts
|

Bulgarian Agriculture and EU Accession

Abstract: This article analyses markets, income and agricultural policy changes in Bulgaria after its accession to the EU. A country AG-MEMOD model, consisting of 18 commodities organised in four sub-models (crops, livestock, milk & dairy and a link between crops and livestock) is applied. The model is an econometric, dynamic, partial-equilibrium and multi-product one. In order to examine the policy environment in Bulgaria, two scenarios are designed: baseline or non-accession (N-Ac) and accession (Ac). The accession sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Similar estimations were conducted by Erjavec (2006), based on partial equilibrium modelling for 1973-2000 data, forecasting that the CEE countries will gain from higher prices and budgetary support, indicating real improvements in most agricultural sectors on recent production levels. Ivanova et al (2007) analysed Bulgarian agriculture after EU accession also by a partial equilibrium model based on data for 1992-2000 and found that accession would have a very positive effect on the crop sector in Bulgaria, whereas the effect is the opposite on the livestock sector. Ciaian and Swinnen (2006) analysed the capitalisation of subsidies in land prices in Central and Eastern Europe with partial equilibrium modelling for 1992-2005 data and concluded that decoupling of payments shifts policy rents from landowners to farmers, but constrains productivity-enhancing restructuring.…”
Section: Literature Review Cee Agriculture: Evidence From the Pastmentioning
confidence: 99%
“…Similar estimations were conducted by Erjavec (2006), based on partial equilibrium modelling for 1973-2000 data, forecasting that the CEE countries will gain from higher prices and budgetary support, indicating real improvements in most agricultural sectors on recent production levels. Ivanova et al (2007) analysed Bulgarian agriculture after EU accession also by a partial equilibrium model based on data for 1992-2000 and found that accession would have a very positive effect on the crop sector in Bulgaria, whereas the effect is the opposite on the livestock sector. Ciaian and Swinnen (2006) analysed the capitalisation of subsidies in land prices in Central and Eastern Europe with partial equilibrium modelling for 1992-2005 data and concluded that decoupling of payments shifts policy rents from landowners to farmers, but constrains productivity-enhancing restructuring.…”
Section: Literature Review Cee Agriculture: Evidence From the Pastmentioning
confidence: 99%
“…Similar estimations were conducted by Erjavec et al (2006), who forecast that the newly accessed Member States would gain from higher prices and budgetary support, indicating real improvements in most agricultural sectors over recent production levels. Ivanova et al (2007) analysed Bulgarian agriculture following EU accession using the AGMEMOD model and found that accession would have a very positive effect on the crop sector in Bulgaria, whereas the effect on the livestock sector would be the opposite.…”
Section: Competitiveness Of Ceec Agriculture Following Eu Enlargementmentioning
confidence: 99%
“…Vaccination against lumpy skin diseases (since 2017) and against bluetongue (since 2016) is being introduced (Slette, Boshnakova, 2018; Jolović & Bobera, 2019). During this period, there were non-tariff export restrictions and negotiations were underway to list dairy exports to the EU, at that time only three Bulgarian companies were involved (Ivanov, 2007;Ivanova et al, 2007). An increase in consumption and production of yoghurt has been noticed compared to the overall growth of the milk market.…”
Section: Resultsmentioning
confidence: 99%